Literary Production of Short Stories using Artificial Intelligence and Its Impact on Teaching and Learning - Santiago Otero-Potosí (Journal of information systems engineering & management, 2025)
Artificial Intelligence (AI) has significantly transformed literary production by offering a variety of applications, from writing assistants to full content generators enabling the comprehension and generation of coherent and captivating texts, these advances have led to explore new narrative forms and offer creative perspectives to writers, interactive stories represent an innovative strategy in the teaching-learning process, Adapting to the needs of digital generations by stimulating the imagination, creativity and cognitive development of readers while promoting social skills such as empathy and problem solving, their interactivity allows them to participate in the development of the plot, make decisions and experience different endings, which increases their motivation and commitment to learning. In this research we used a methodology of systematic review of specialized literature on the subject and the descriptive method in a transversal way, concluding that the convergence of Artificial Intelligence and interactive stories represents a significant milestone in literary production and education, expanding the creative possibilities by allowing the understanding, generation of texts and images in an autonomous way.